KAJIAN TENTANG PERANCANGAN ALAT PEWARNAAN HAPUSAN BERBASIS MIKROKONTROLER - Yori Yori; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Designed system is a tool used for staining blood smears automatically. This system will produce output in the form of blood smear preparations that had been stained with Wright fluid.  The process of taking blood and manufacture of blood smear preparations made by the medical officer, then the process of staining blood smear preparations will be designed automatically on this thesis. The results of the coloring stage will be integrated with the microscope and aids detection and recognition of white blood cells automatically have been developed previously. Key wordsAlat Bantu, pewarnaan, Mikrokontroler, Sel Darah, Sel Darah Putih, Sel Darah Merah.